A study to evaluate HbA1C as an independent diagnostic criterion comparing to fasting plasma glucose and postprandial glucose levels as a standard test for diagnosis of diabetes - Lalitha R; Surekha B. Shetty; Anil Kumar R. (International Journal of Medical Research and Review, 2018)
Aims and objectives: 1) To compare and correlate glycosylated haemoglobin (HbA1C) as an independent criteria in diagnosis. 2) To define the sensitivity and specificity of HbA1C estimates at the ADA recommended cut off of ≥ 6.5%.Study design and methods: Subjects were first tested for Fasting plasma glucose and two-hours post 75 grams glucose challenge, HbA1c was estimated for the all the subjects.Results: The sensitivity and specificity of HbA1C at the ADA recommended ≥ 6.5% cut off value in newly detected diabetic patients was 96.70% and 82.92%respectively with a positive predicted value of 56.05% and a negative predictive value of99.11 % .75.00 % at a p<0.001.We find that we miss 42% of people with diabetes if fasting plasma glucose levels are considered. Given the risks associated with PPG levels in our population it is important that these criteria be used in screening programmes.Conclusion: Our study shows that HbA1C is comparable to FPG levels estimation but is not superior enough to replace blood glucose estimation. Use of post prandial glucose levels are better in detecting diabetes than fasting plasma glucose levels. A combination of post prandial glucose with HbA1C may be a superior single test that can overcome the cumbersome oral glucose tolerance test.